(untitled) (Biological Sciences - PJSIR, 2006)
The seeds of Citrus reticulata var. Kinnow orange contained 26.0% lipids. The seed oil was examined for its lipids and fatty acids composition. The lipids were fractionated into neutral lipids (96.3%) and polar lipids (3.7%) by thin layer chromatography. The neutral lipids were identified as hydrocarbons (1.2%), wax esters (1.1%), sterol esters (3.2%), triacylglycerols (70.5%), free fatty acids (2.3%), 1,3-diacylglycerols (4.0%), 1,2-diacylglycerols (4.2%), gly- colipids (1.6%), sterols (2.1%), 2-monoacylglycerols (3.1%), and 1-monoacylglycerols (3.0%). The polar lipids were identified as phosphatidyl ethanolamines (1.2%), phosphatidyl cholines (0.8%), lysophosphatidyl ethanolamines (0.6%), and phosphatidyl inositols (1.1%). The fatty acids range of all the esterified lipids was C – C , showing higher 14:0 18:2 percentage of unsaturated fatty acids. The major fatty acids were palmitic, stearic, oleic and linoleic acids.